Membumikan Literasi: Mahasiswa Mengajar Anak Desa Lewat Cerita dan Kreativitas - Daryn, Masayu; Susanti, Fitria; Rafli, Najid (Lembaga Publikasi Ilmiah Nusantara, 2025)
The community service program “Grounding Literacy: University Students Teach Village Children Through Stories and Creativity” aims to increase reading interest and basic literacy skills among children in rural areas through a participatory, creativity-based approach. The background of this initiative stems from limited access to reading materials and the low prevalence of literacy habits in village environments.The implementation method includes a needs-assessment phase, the design of learning modules based on local folklore, training for student volunteers, and the execution of interactive learning activities that integrate art, educational games, and simple writing exercises. Evaluation is carried out through direct observation, interviews with participants and parents, as well as measuring improvements in reading interest and reading comprehension before and after the activities.The results show a significant increase in children’s enthusiasm for reading and writing activities, as well as improved understanding of the moral and cultural values contained in local stories. In addition, the program strengthens social ties between university students and rural communities and fosters a sense of social responsibility among students. This program is expected to serve as a model for community-based literacy development that can be replicated in other regions with adjustments to cultural contexts and local needs.